Older adult perceptions of participation in group-and home-based falls prevention exercise - Robins, L.; Hill, Keith; Day, L.; Clemson, L.; Finch, C.; Haines, T. (Human Kinetics Inc, 2016)
© 2016 Human Kinetics, Inc. This paper describes why older adults begin, continue, and discontinue group-and home-based falls prevention exercise and benefits and barriers to participation. Telephone surveys were used to collect data for 394 respondents. Most respondents reported not participating in group-(66%) or home-based (78%) falls prevention exercise recently. Reasons for starting group-based falls prevention exercise include health benefits (23-39%), health professional recommendation (13-19%), and social interaction (4-16%). They discontinued because the program finished (44%) or due to poor health (20%). Commonly reported benefits were social interaction (41-67%) and health (15-31%). Disliking groups was the main barrier (2-14%). Home-based falls prevention exercise was started for rehabilitation (46-63%) or upon health professional recommendation (22-48%) and stopped due to recovery (30%). Improvement in health (18-46%) was the main benefit. These findings could assist health professionals in prescribing group-based falls prevention exercise by considering characteristics of older adults who perceive social interaction to be beneficial.